Champ4life Study Protocol: A One-Year Randomized Controlled Trial of a Lifestyle Intervention for Inactive Former Elite Athletes with Overweight/Obesity - Silva, Analiza M.; Nunes, Catarina L.; Matias, Catarina N.; Jesus, Filipe; Francisco, Rúben; Cardoso, Miguel; Santos, Inês; Carraça, Eliana V.; Silva, Marlene N.; Sardinha, Luís B.; Martins, Paulo; Minderico, Cláudia S. (Nutrients, 2020)
Preventive and educational programs directed to former elite athletes in the areas of healthy living are required. This is particularly relevant as obesity and health-related problems are observed in retired athletes, especially in those whose current levels of physical activity are below the recommendations. During their sports career, elite athletes are supported by a multidisciplinary team; upon retirement, no support is provided for the transition to a different lifestyle. So far, no program has been implemented to promote sustained healthy lifestyle behaviors in the post-career transition and evidence is lacking for such an intervention. Firstly, we aim to determine if Champ4life, a 1-year lifestyle intervention targeting inactive former athletes with overweight and obesity, is effective for reducing total and abdominal fat. Secondly, our purpose is to assess the effectiveness of the intervention on the levels of physical activity and sedentary behavior, resting energy expenditure, cardio-metabolic markers, physical fitness, energy balance components, eating self-regulation markers, and quality of life over 12 months. Champ4life is an evidence- and theory-based program using a randomized control trial design (intervention vs. control group) that will be conducted on 94 inactive former elite athletes with overweight and obesity. The first four months of the Champ4Life program include a nutritional appointment and 12 weekly, 90-min sessions. Classroom sessions seek to provide participants with key information and a toolbox of behavior change techniques to initiate and sustain long-term lifestyle changes. Participants will undergo baseline, 4-month, and 12-month measurements of body composition (primary outcomes), resting energy expenditure, physical fitness, metabolic markers, energy balance related-markers, and quality of life (secondary outcome). This trial will provide evidence on the effectiveness of the Champ4life program, a pioneer lifestyle intervention for retired athletes, offering tools for sustained changes in physical activity, sedentary behavior and diet, aiming to improve body composition and overall health-related markers.